Biomimetic engineering of materials based on hagfish slime thread proteins - Fu, Jing (2017)
Biomimetic materials inspired from Nature have shown unique potential to create a new class of materials with a set of properties not found in synthetic materials. Silk, one classical example of biological protein-based materials, exhibits excellent mechanical performances for diverse applications. However, it suffers from drawbacks with regard to bioengineering processing. Another promising –but far less explored– biological fibrous material model is the hagfish slime thread, which in the native state can be as stiff and tough as silks. At the molecular level, hagfish slime threads (from the species Eptatretus stoutii, Es) are built from α-helical coiled-coil proteins (EsTKα and EsTKγ), which self-assemble into hetero-dimeric intermediate filaments (IFs), and these IFs are bundled intra-cellularly with a high degree of axial alignment into macroscopic threads. Upon draw-processing, native hagfish slime threads exhibit an irreversible structural transition from α-helical coiled-coil to aligned β-sheet (α to β transition). This strain-induced phase transformation endows native threads with remarkable mechanical properties that rival silks and approach Kevlar.